The effect of foliar application of Abscisic acid on growth of wheat plant under different levels of water stress: بسمة عزيز حميد الدعمي سناء خادم عبد الامير الفتلاوي - حميد الدعمي بسمة عزيز; عبد الامير الفتلاوي سناء خادم (Journal of Kerbala for Agricultural Sciences, 2015)
This study was conducted using plastic pots in the Department of Biology, College of Education for Pure Science - University of Karbala during the growing season of 2013/2014. Factorial experiment within a Completely Randomized Design (C.R.D.) with three replicates was applied . The experiment included three concentrations of Abscisic acid (i.e. 0, 50 and 70) mg.l-1 .and three levels of field capacity (i.e. 50 , 75 and 100%). The experiment included 27 pots (experimental units).Results were summarized as follow : the field capacity of 100% gave the highest values of the remain studied traits. Whereas , 50% field capacity gave the lowest values root lenght. Apart from one case, Abscisic acid effect was constant with all studied parameters, where 70 mg.l-1. Abscisic acid gave the highest values of the parameters All interactions between water stress levels and Abscisic acid had a pronounced effect on studied parameters.